2018
DOI: 10.1093/rheumatology/key219
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking in childhood increases the risk of developing rheumatoid arthritis

Abstract: This study confirms that active smoking is associated with an increased risk of RA. It suggests for the first time that passive exposure to tobacco during childhood might also increase the risk of RA in future light smokers and probably non-smokers. Our results highlight the importance of avoiding any tobacco environment in children, especially in those with a family history of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 21 publications
3
37
2
Order By: Relevance
“…Thus, high levels of passive smoke exposure may place individuals at higher risk for RA, even among smokers. This finding may explain why an association of passive smoking with RA was suggested in 2 other studies, especially among individuals with a longer duration of exposure extending back to childhood (10,18).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, high levels of passive smoke exposure may place individuals at higher risk for RA, even among smokers. This finding may explain why an association of passive smoking with RA was suggested in 2 other studies, especially among individuals with a longer duration of exposure extending back to childhood (10,18).…”
Section: Discussionmentioning
confidence: 61%
“…In a large meta‐analysis that included 11 studies , 13,885 RA cases among a total of 593,576 individuals, current‐smokers had an odds ratio (OR) of 1.64 for seropositive RA compared to never‐smokers. Recent results from the French E3N cohort study in which 71,248 women were prospectively followed since 1990 showed that past‐smokers (HR 1.32, 95% CI 1.06‐1.64) and current‐smokers (HR 1.57, 95% CI 1.13–2.19) had an increased RA risk compared to never‐smokers . Our group previously investigated smoking performed only in the NHS using follow‐up data from 1976 to 2002 and demonstrated that current‐ smokers had an HR of 1.46 (95% CI 1.20–1.79) for all RA and HR of 1.58 (95% CI 1.21–2.06) for seropositive RA compared to never‐smokers .…”
Section: Discussionmentioning
confidence: 93%
“…Although the etiology of rheumatoid arthritis (RA) remains obscure, previous studies have implicated smoking as an important and potentially modifiable risk factor for the development of RA . Previous epidemiologic studies have identified cigarette smoking as one of the most important lifestyle risk factors for the development of RA and particularly seropositive RA, which is defined as the presence of rheumatoid factor (RF) or anti–cyclic citrullinated peptide (anti‐CCP) .…”
Section: Introductionmentioning
confidence: 99%
“…Given previous associations of active and passive smoking with risk of COPD , asthma , and RA , adjustment for those was an important aspect of our analysis. On the baseline questionnaire, participants reported smoking status (never/past/current) and age at which they started smoking.…”
Section: Methodsmentioning
confidence: 99%